Modification of magnetic molybdenum disulfide by chitosan/carboxymethylcellulose with enhanced dispersibility for targeted photothermal-/chemotherapy of cancer. Issue 7 (29th January 2021) - Xie, Meng; Li, Jiaqian; Deng, Tongtong; Yang, Na; Yang, Mei
Abstract : mMoS2 –CS/CMC with enhanced stability and intratumoral accumulation was synthesized for targeted photothermal-chemo combination therapy. Abstract : In this work, magnetic molybdenum disulfide (mMoS2 ) was synthesized firstly. Then, layer-by-layer (LbL) self-assembly technology was used for the preparation of chitosan/carboxymethylcellulose functionalized mMoS2 nanocomposites. The nanocomposites with the diameter of 0.4 μm did not easily agglomerate in biological suspensions, thus had good dispersion and stability. Simultaneously, mMoS2 –CS/CMC strongly inhibited the adsorption of non-specific proteins to mMoS2 . In a drug loading experiment, in which doxorubicin hydrochloride (DOX) was used as a model drug, it was found that the drug loading capacity of mMoS2 –CS/CMC was high and the drug loading rate could reach 86%. When the drug was released, mMoS2 –CS/CMC–DOX showed an obvious pH-dependent release behavior. In cellular studies, the nanocomposites were easily taken up by tumor cells, and mainly located in the cytoplasm. The pure carrier materials had good biocompatibility with no obvious cytotoxicity, but they could cause dose-dependent cytotoxicity after DOX loading. Moreover, mMoS2 –CS/CMC had an excellent photothermal effect, and an in vivo study showed that after it was injected into mice, more nanocomposites concentrated in the tumor site than mMoS2, indicating the tumor targeting properties. Therefore, the modification of mMoS2 with chitosan and sodium carboxymethylcellulose will promote the development of tumor therapy.